1996
DOI: 10.1080/15513819609168713
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values for Singleton and Twin Placental Weights

Abstract: The largest series of normal singleton placental weights was collected in the Collaborative Perinatal Study between the years 1959 and 1966 but values for normal twin placental weights were not published. In our study we examined 787 singleton and 514 twin normal placentas. Placentas with associated conditions known to affect the weights of placentas were excluded. After establishing the normal values for singleton and twin placental weights, we concluded that weight gain of twin placentas appears to accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
144
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(149 citation statements)
references
References 5 publications
4
144
0
1
Order By: Relevance
“…We assume that part of this group comprehends cases with ''placental bed pathology'' as cause due to sampling error [37]. Moreover, dependent on the references used for placental weight and placenta/birth weight ratios, allocation of placental hypoplasia can vary [18,38]. To improve validity of statistics, uniformity of definitions of these large placental subgroups are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that part of this group comprehends cases with ''placental bed pathology'' as cause due to sampling error [37]. Moreover, dependent on the references used for placental weight and placenta/birth weight ratios, allocation of placental hypoplasia can vary [18,38]. To improve validity of statistics, uniformity of definitions of these large placental subgroups are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Small for gestational age (SGA) was defined as birth weight <10th percentile [17]. Placenta hypoplasia was defined as an absolute too low placenta weight <10th percentile and/or a too low placenta/birth weight ratio [18]. We defined placental bed pathology for preterm cases as any infarctions found at placental histology and for term cases as extensive infarction that affected >10% of the placental area [19].…”
Section: Methodsmentioning
confidence: 99%
“…There is a positive relationship between birthweight and placental weight (Bleker et al, 1979;Falkner, 1986;Knaus 1949;McKeown & Record, 1953;Naeye, 1987;Thomson et al, 1969;Victoria et al, 2001). Furthermore, low placental weight can often be related to adverse perinatal outcome (Bonds et al, 1984;Naeye, 1987;Pinar et al, 1996). Compared to singletons, twins are born earlier, have lower birthweights and smaller placentas (Bleker et al, 1979).…”
mentioning
confidence: 99%
“…Since 1953, at least five studies presented the progress of placental weight in multiple gestations (Bleker et al, 1979(Bleker et al, , 1988McKeown & Record, 1953;Pinar et al, 1996;Ward, 1985; Table 1). Two of these studies presented a smoothed curve and found that placental weight was not influenced by sex and chorionicity (Bleker et al, 1988;Pinar et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation